¿Nos encontramos frente a una nueva clase de mutagenos? - Cuyubamba, Oscar R.; Pryor, William; Shane, Barbara S.; Squadrito, Giuseppe (Pontificia Universidad Católica del Perú, 1990)
1,3-Dinitronaphthalene, previous1y identified in particulate organic matter, easily forms covalent adducts with DNA nucleotides at room temperature. The mutagenic potency of a related dinitropolycyclic aromatic hydrocarbon (dinitroPAH) with meta disubstitution, namely 1,3-dinitrofluoranthene, is rather independent of the Salmonella Typhimurium tester strain (TA98, TA98NR and TA98/l, 8DNP6) when assayed according to the Ames Test. This unusual behavior suggests that it does not require metabolic activation via the "classical nitroreductase" and/or the acetylase. The fact that 1,3--dinitronaphthalene readily forms covalent adducts with DNA nucleotides further suggests that dinitroPAH with meta nitro-groups may not require the usual metabolic activation pathways.

El 1 ,3-dinitronaftaleno, previamente identificado en polvo ambiental, forma aductos covalentes con nucleótidos del DNA a temperatura ambiente fácilmente. La potencia mutagénica de un hidrocarburo aromático policíclico dinitrado (HAPDN), el 1, 3-dinitrofluoranteno, es prácticamente independiente de la cepa de Salmonella Typhimurium (TA98, TA98NR y TA98/1, 8DNP6) empleada en el Test de Ames. Este comportamiento poco usual sugiere que este HAPDN no requeriría de la activación metabólica vía la "nitroreductasa clásica" y/o de la acetilasa El hecho de que el 1, 3- dinitronaftaleno forma aductos covalentes con nucleótidos del DNA rápidamente está de acuerdo con que HAPDN meta disubstituídos podrían prescindir de las rutas usuales de activación metabólica.
Keywords: Biology; ADN; Química; Biologia; https://purl.org/pe-repo/ocde/ford#1.04.00